Thermo - chemical of solid carboneous waste - 271119 Ramvir Ram Nekeram (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1999